2011
DOI: 10.1111/j.1365-2125.2011.04002.x
|View full text |Cite
|
Sign up to set email alerts
|

How to manage hypertension in pregnancy effectively

Abstract: The hypertensive disorders of pregnancy (HDP) are a leading cause of maternal mortality and morbidity in both well and under-resourced settings. Maternal, fetal, and neonatal complications of the HDP are concentrated among, but not limited to, women with pre-eclampsia. Pre-eclampsia is a systemic disorder of endothelial cell dysfunction and as such, blood pressure (BP) treatment is but one aspect of its management. The most appropriate BP threshold and goal of antihypertensive treatment are controversial. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 54 publications
2
85
0
11
Order By: Relevance
“…Almost all studies suggested about alpha methyldopa (centrally acting sympathoplegic), nifedipine (calcium channel blocker) and labetalol ( -adrenoceptor blocker). There is ongoing debate about whether antihypertensive therapy impairs intra-uterine fetal growth, and if so, whether this effect is restricted to -adrenoceptor blocker therapy [8]. …”
Section: Methodology Resultsmentioning
confidence: 99%
“…Almost all studies suggested about alpha methyldopa (centrally acting sympathoplegic), nifedipine (calcium channel blocker) and labetalol ( -adrenoceptor blocker). There is ongoing debate about whether antihypertensive therapy impairs intra-uterine fetal growth, and if so, whether this effect is restricted to -adrenoceptor blocker therapy [8]. …”
Section: Methodology Resultsmentioning
confidence: 99%
“…The bulk of evidence relates to use of parenteral hydralazine or labetalol, and oral nifedipine, labetalol or methyldopa [Magee, 2011]. It is essential to keep the blood pressure in the normal range.…”
Section: Pregnancy Category Xmentioning
confidence: 99%
“…Consequently, there is an increased risk of morbidity and mortality of both mother and baby (5). In order to reduce the occurrence and severity of these hemodynamic complications, many drugs such as hydralazine (6), magnesium sulfate (7), labetalol (8), fentanyl (5), trimethaphan (2), sodium nitroprusside (9), lidocaine (10), nitroglycerin (11,12), and nifedipine (13) have been used with varying degrees of success. Hydralazine has been the antihypertensive of choice for women with severe hypertension in pregnancy for many years (14,15).…”
Section: Attenuation Of Cardiovascular Response In Severe Preeclampsiamentioning
confidence: 99%